Phlegcarines A-C, three Lycopodium alkaloids from Phlegmariurus carinatus (Desv. ex Poir.) Ching. (February 2023) - Thamnarak, Wanlaya; Thaisaeng, Wachirasak; Batsomboon, Paratchata; Eurtivong, Chatchakorn; Wannarit, Nanthawat; Ruchirawat, Somsak; Thasana, Nopporn
Abstract: Three undescribed Lycopodium alkaloids, phlegcarines A-C, along with nine known alkaloids, were isolated from the aerial parts of a gardening clubmoss Phlegmariurus carinatus (Desv. ex Poir.) Ching. Phlegcarine A is an undescribed Lycopodium alkaloid possessing an unprecedented 5/9/6/6 fused-tetracyclic ring system consisting of an oxa-cyclononanone, a piperidine, a methylcyclohaxane and an oxazolidine. Phlegcarine B is the first N -chloromethyl piperidinium Lycopodium alkaloid of (+)-lycoflexine. The semi-synthesis of phlegcarine B was investigated from (+)-fawcettimine. Phlegcarine C, an undescribed epimer of 12-epilycodoline, is a rare lycopodine-type alkaloid with β-oriented H-4. Transformation of phlegcarine C and lycodoline to 12-epilycopodine N -oxide via keto-enol tautomerization was investigated using m -CPBA. The structural assignments were established through comprehensive spectroscopic techniques and chemical correlations. Phlegcarines A-C were assayed for their anti-acetylcholinesterase activity, but none of them exhibited biological activity more potent than that of huperzine A. Graphical abstract: Three undescribed Lycopodium alkaloids, phlegcarines A-C, were isolated from Phlegmariurus carinatus and the postulated biomimetic synthesis of phlegcarine B was investigated as well as the transformation of phlegcarine C. Image 1 Highlights: Twelve Lycopodium alkaloids, including three undescribed phlegcarines A-C, were isolated from Phlegmariurus carinatus. A facile synthesis of phlegcarine B is accomplished in two steps from isolated (+)-fawcettimine. Phlegcarine C and lycodoline are transformed to 12-epilycopodine N -oxide via keto-enol tautomerization.